Frequency of psychological disorders in under 15 years old children with thalassemia major and intermediate in Tabriz children’s hospital - Amir Ataollah Hiradfar; Seyyed Gholamreza Noorazar (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2021)
Background: Thalassemia is the most common hemoglobinopathy, worldwide. Chronicity and complications of thalassemia can affect the quality of life in these patients. Psychological aspects of transfusion-dependent forms of thalassemia (major and intermediate) are well-known, especially in adults. Aim of this study was to investigate the prevalence of mental disorders in thalassemia major and intermediate who were under 15 years old. This study was organized in thalassemia clinic in Tabriz Children’s Hospital from June 2014 to August 2014. Methods: Sixty transfusion-dependent thalassemia patients were eligible in our study. Twenty-six patients were boys and 34 were girls. Mean age of the participants were 9 ±1. A standard questionnaire called K-SADS was used to collect the data during interview by patients and their parents. In this research, the data have been analyzed to demonstrate the prevalence of psychologic disorders and the relationship between psychologic disorders and demographic characteristics. Results: The prevalence of psychological disorders in our study was: ODD (37%), social phobia (20%), depression (18%), conduct disorders (10%), and enuresis (5%). Also, psychologic disorders had a significant relationship with age and education. Conclusion: Our study confirmed that about 80% of the participants had one of the psychological disorders. Therefore, a regular psychologic consulting for children and their parents in thalassemia clinics is required.